Analisis kesegaran dan kandungan formalin pada ikan laut di Lampung Selatan - Arafah, Purnama; Nurhayati, Tati; Suseno, Sugeng Heri; Ardina, Carissa Mutiara; Suhaima, Nurafi Razna (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Formaldehyde contamination from the illegal use of formalin and natural accumulation is an indicator of fish quality decline throughout the post-harvest supply chain, from capture to distribution to consumers. This study aimed to determine the level of freshness and formaldehyde content in seawater fish in the fisheries supply chain (TPI Dermaga Bom and traditional markets) in Kalianda, South Lampung. The methods used included organoleptic analysis, pH measurement, total volatile base (TVB) measurement, trimethylamine (TMA) measurement, active formaldehyde (FA) measurement, and dimethylamine (DMA) measurement. Samples of snapper, mackerel, sardines, and semar were analyzed to compare their quality. The results showed that fish samples from the collectors were fresher than those from traditional markets. The pH values at both locations ranged from 6.39 to 7.12. The TVB values of both locations ranged from 12.55 to 30.98 mgN/100 g, while the TMA values ranged from 8.82 to 12.35 mgN/100 g. The FA values at both locations ranged from 0.25 to 0.45 ppm, whereas the DMA values ranged from 0.54 to 0.67 ppm. Statistical results showed that the p-value was greater than 0.05 in the TVB and TMA tests between fish from collectors and markets, indicating that there was no significant difference between the two locations. However, no significant differences were observed in the pH values, natural formaldehyde content, or dimethylamine levels. The implications of these research results are expected to help improve fish quality management and support strict monitoring policies in the fishery product supply chain in the future.